2011
DOI: 10.1099/jmm.0.031476-0
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological findings and antimicrobial resistance in odontogenic and non-odontogenic chronic maxillary sinusitis

Abstract: The main objectives of this study were to estimate the frequency of chronic maxillary sinusitis of dental origin, and to evaluate the microbiology of odontogenic and non-odontogenic chronic maxillary sinusitis. Aspirates from 59 patients with chronic maxillary sinusitis (47 non-odontogenic, 12 odontogenic), collected during a 3-year period, were microbiologically processed for aerobic and anaerobic bacteria. Moreover, antimicrobial susceptibility was evaluated in the isolated bacteria. In this study, 20 % of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0
8

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(100 citation statements)
references
References 27 publications
3
89
0
8
Order By: Relevance
“…44 Recently, evidence of cytokine and chemokine mRNA expression in canine sino-nasal aspergillosis and idiopathic LPR has determined that these two conditions have different and distinct pathophysiology and low grade occult fungal disease is not likely the cause for LPR. 20 A sinusitis study identified predominate anaerobic isolates in 71% of periapical infections as well as anaerobic isolates in 76% and 79% of acute and chronic sinusitis cases, respectively. 45,46 Based on cytokine and mRNA, other fungal organisms suspected (Alternaria and Cladosporium species) are likely not involved.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…44 Recently, evidence of cytokine and chemokine mRNA expression in canine sino-nasal aspergillosis and idiopathic LPR has determined that these two conditions have different and distinct pathophysiology and low grade occult fungal disease is not likely the cause for LPR. 20 A sinusitis study identified predominate anaerobic isolates in 71% of periapical infections as well as anaerobic isolates in 76% and 79% of acute and chronic sinusitis cases, respectively. 45,46 Based on cytokine and mRNA, other fungal organisms suspected (Alternaria and Cladosporium species) are likely not involved.…”
Section: Figurementioning
confidence: 97%
“…In published case series reports and retrospective studies, the differential diagnosis list often does not include dental/oral pathology, whereas in a few studies "periodontal disease" or "tooth abscess" are listed in the discussion and introductions but they do not explore the significance of these pathologies any further. 11,13,14,[18][19][20][21][22][23] Respiratory mucosal pathology occurs secondary to periodontal and endodontic infections. Similar challenges exist in human odontogenic maxillary sinusitis (OMS).…”
Section: Introductionmentioning
confidence: 99%
“…We found that half of OS have maxillary and anterior ethmoid sinusitis. In these cases, the anterior ethmoiditis is probably the result of proximity of the maxillary sinus ostium and those of anterior ethmoid sinuses, which facilitate ethmoid inflammation from an infected maxillary sinus (20). Presumably, another crucial factor is related to the time factor, being that the longer evolutionary presents a maxillary sinusitis, more likely is that inflammation spreading to anterior ethmoid sinus causing an anterior ethmoid sinusitis.…”
Section: Discussionmentioning
confidence: 99%
“…13 Information on the antimicrobial susceptibility of these species is limited. 2,14 Infections caused by G. morbillorum have been cured by antibiotic therapy, usually using a combination of penicillin and aminoglycoside. In the penicillinresistant or penicillin-allergic patient, monotherapy or a combination of other antibiotics, such as vancomycin or erythromycin plus rifampicin, have been effective.…”
Section: Discussionmentioning
confidence: 99%